Population dynamics and human–Primate interactions at a cultural heritage forest site: Implications for conservation education - Siti Rukayah; Sri Riani; Nadhilla Haura Wahyudiana; Esa Rinjani Cantika Putri; Rosyid Ridlo Al-Hakim; Erie Kolya Nasution; Fajarani Fitriasih; Mahmmoud Hussein Abdul Rahman (University of Muhammadiyah Malang, 2025)
Long-tailed macaques represent a compelling model for ethnoprimatological research in human-influenced and culturally significant ecosystems. This study evaluated population dynamics, social structure, and behavior of Macaca fascicularis inhabiting a 0.8-hectare secondary forest enclave surrounding a religious heritage site in Central Java, Indonesia. Three two-week census periods conducted from 2021 to 2023 documented temporal fluctuations in troop size (96–125 individuals), subgroup formation, and behavioral responses associated with provisioning, resource availability, and human presence. These demographic and behavioral patterns highlight the adaptive strategies that enable macaques to persist in fragmented cultural landscapes, while also revealing pressures linked to crowding, reliance on anthropogenic foods, and occasional conflict with visitors and surrounding communities. Beyond their ecological relevance, the findings provide evidence-based insights that can be integrated into environmental and conservation education. The documented interactions between macaques, caretakers, and visitors offer concrete examples for developing educational materials, improving visitor guidelines, and promoting awareness of responsible wildlife behavior at sacred forest sites. This study establishes a baseline for long-term monitoring and demonstrates how ecological data from cultural heritage forests can support conservation learning and sustainable human–wildlife coexistence.